Preparation and Characterization NiMo/Zeolite Catalyst using Microwave Polyol Process Method for Synthesizing Renewable Diesel from Jathropa Oil - Bambang Heru Susanto (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Biofuels have great potential to fulfill the energy needs of Indonesia. The process used is hydrodeoxygenation reaction (HDO) whose products are known as renewable diesel. This study focuses on preparation NiMo/Zeolite catalyst for synthesizing renewable diesel from jatropha oil. Preparation of NiMo/Zeolite catalyst is done by using microwave polyol process method. Microwave polyol method is a modification from incipient wetness method to overcome energy consumption and preparation time problem. Microwave polyol method is done by using a fast and uniform electric radiation from microwave as heating medium to dry catalyst. The catalyst result by using microwave polyol method gives the surface area of ​​5.45m2/g and has average crystal size of 62.98nm. NiMo/Zeolit catalyst used to synthesize renewable diesel at 375oC, pressure 12 bar, catalyst loading 1% mass of Jathropa Oil and stirer speed 800 rpm. Based on the characterization results of GC-MS, the catalyst NiMo/Zeolit has conversion of jatropha oil 88,61% with renewable diesel product selectivity and yield are 35.26 and 21.5% respectively. According to result of FTIR and product physical properties, renewable diesel products have similar functional group and have better specifications than commercial diesel with density values​​: 0.833 gr/cm3, viscosity: 3.02 cst, cetane index: 61.01